Śravaṇabeḷgoḷa : rājakīya, sāhityika, sāṃskrtika mahatva - Śirūra, Bi. Vhi., 1941- (Research publications series (Karnatak University) ;, 1976)
On the importance of Srāvana Belgola, Jain pilgrimage center, in the history of Kannada literature and culture; a study.